Vagus nerve stimulation: a new promising therapeutic tool in inflammatory bowel disease. (18th April 2017) - Bonaz, B.; Sinniger, V.; Pellissier, S.
Abstract: Inflammatory bowel disease (IBD), that is Crohn's disease (CD) and ulcerative colitis, affects about 1.5 million persons in the USA and 2.2 million in Europe. The pathophysiology of IBD involves immunological, genetic and environmental factors. The treatment is medico‐surgical but suspensive. Anti‐TNFα agents have revolutionized the treatment of IBD but have side effects. In addition, a non‐negligible percentage of patients with IBD stop or take episodically their treatment. Consequently, a nondrug therapy targeting TNFα through a physiological pathway, devoid of major side effects and with a good cost‐effectiveness ratio, would be of interest. The vagus nerve has dual anti‐inflammatory properties through its afferent (i.e. hypothalamic–pituitary–adrenal axis) and efferent (i.e. the anti‐TNFα effect of the cholinergic anti‐inflammatory pathway) fibres. We have shown that there is an inverse relationship between vagal tone and plasma TNFα level in patients with CD, and have reported, for the first time, that chronic vagus nerve stimulation has anti‐inflammatory properties in a rat model of colitis and in a pilot study performed in seven patients with moderate CD. Two of these patients failed to improve after 3 months of vagus nerve stimulation but five were in deep remission (clinical, biological and endoscopic) at 6 months of follow‐up and vagal tone was restored. No major side effects were observed. Thus, vagus nerve stimulation provides a new therapeutic option in the treatment of CD. Abstract : Content List – Read more articles from the symposium: 13th Key Symposium – Bioelectronic Medicine: Technology Targeting Molecular Mechanisms.